Parmenides and Wittgenstein - Kubok, Dariusz (Folia Philosophica, 2001)
The paper is an attempt at comparing the ideas of Parmenides of Elea and Wittgenstein from the time of Tractatus logico-philosophicus. Numerous scholars (Popper, Mourelatos. Wolniewicz, Gawroński, Blandzi) point to an affinity of Parmenides’s certain findings with L. Wittgenstein’s philosophy of language. The problems approached by them (the relationship of thought to the world, the problem of the limits and the nature of thinking) seem to confirm the assumption of the existence of some parallels between those philosophers. It should be remembered, however, that their views on the subject of philosophy and its status were different. What cannot be questioned is the fact that they both were the “philosophers of problems” who asked fundamental questions and with a comparable eagerness were trying to answer them.